Pendampingan Penguatan Profil dan Kurikulum Berbasis Keunggulan di SDU Permata Muhammadiyah Lima Karangploso Malang - Husamah, Husamah; Rahardjanto, Abdulkadir; Lestari, Nurdiyah (Jurnal SOLMA, 2025)
Background: SDU Permata Mulia is faced with a big challenge to be able to compete and survive amidst the competition of educational institutions and the increasing selectivity of parents in choosing the best school/educational institution for their children. Efforts are needed to strengthen the school by compiling a profile, curriculum, PjBL theme, and branding the school through mass media. This community service activity aims to provide assistance in Strengthening the Profile and Curriculum Based on Excellence at SDU Permata Mulia to produce an agreed outcome. Method: Permanent participants in the activity are the principal and teachers, totaling 12 people. Certain activities are also attended by the Muhammadiyah Branch Leadership, parents of students, and the school's Board of Trustees. Activities are carried out in the form of training (delivery of materials), practice, and assistance until a product is produced. Data is obtained by documenting activities and products. Funds are analyzed using qualitative descriptive methods. Results: (1) a workshop on compiling and determining the school profile, (2) a workshop on compiling and determining the curriculum; (3) the PjBL Phase A theme was produced and (4) the publication/promotion of school activities through mass media. Conclusion: Producing can important achievements, including the preparation of a school profile as a strategic promotional tool, the development of an innovative curriculum that is in line with 21st century competencies and Islamic values, the implementation of relevant PjBL themes for meaningful learning, and journalism training for teachers that strengthen school branding through news publications in various media.